A novel class of copper(II)- and zinc(II)-bound non-steroidal anti-inflammatory drugs that inhibits acute inflammation in vivo. Issue 1 (December 2016) - Puranik, Rajesh; Bao, Shisan; Bonin, Antonio; Kaur, Ravinder; Weder, Jane; Casbolt, Llewellyn; Hambley, Trevor; Lay, Peter; Barter, Philip; Rye, Kerry-Anne
Abstract Background The ability of Zn(II) and Cu(II) metal complexes of non-steroidal anti-inflammatory drugs (NSAIDs) to inhibit acute arterial inflammation in vivo has been studied. Results When acute vascular inflammation was induced in normocholesterolemic New Zealand White rabbits by inserting a non-occlusive silastic collar around the common carotid artery, a single oral dose of Cu(II)-indomethacin (Cu(II)Indo, 3 mg/kg) administered by laparotomy achieved a 67 % (8.2 ± 1.7 vs. 2.7 ± 0.4 image units, p < 0.05) reduction in endothelial expression of vascular cell adhesion molecule-1 (VCAM-1) but did not inhibit endothelial intercellular adhesion molecule (ICAM-1) expression significantly. Treatment with Cu(II)-acemetacin (Cu(II)ACM, 3 mg/kg) led to a profound 88 % (8.2 ± 1.7 vs. 1.0 ± 0.5 image units, p < 0.01) reduction in endothelial VCAM-1 expression but did not inhibit ICAM-1 expression, while treatment with Zn(II)-acemetacin (Zn(II)ACM, 3 mg/kg) led to an 84 % (19.3 ± 1.0 vs. 3.1 ± 1.2 image units, p < 0.01) reduction in endothelial ICAM-1 expression and did not inhibit VCAM-1 expression. No adverse gastric, hepatic or renal effects were observed in treated animals. Conclusion These findings provide the "proof of concept" that this novel class of drug, where there is complexation of NSAIDs with metal ions, has substantial anti-inflammatory effects in an animal model of acute vascular inflammation with the possibility of low rates of adverse effects.